A revision of Clerodendrum smitinandii (Lamiaceae): floral morphology, pollen structure and distribution - Satthaphorn, Jiratthi; Paton, Alan J.; Nuraliev, Maxim S.; Phuphumirat, Wongkot; Tagane, Shuichiro; Leeratiwong, Charan (Phytotaxa, 2025)
A comprehensive morphological and taxonomic revision of Clerodendrum smitinandii (Clerodendrum section Albiflora, Ajugoideae, Lamiaceae) is presented. The species is shown to be distributed in southeastern Thailand, Cambodia, and southern Vietnam. An earlier reported specimen from Vietnam is proved to be misidentified; hence the first unambiguous report of the species in this country is provided here. Its conservation status is assessed as Least Concern (LC). Floral and pollen morphology of C. smitinandii are first described based on recent collections and historical herbarium specimens. A comparison of C. smitinandii with the morphologically closest species, C. nhatrangense, is provided. A complete list of available specimens, a distribution map, images of the holotype and isotype, colour photographs of living plants, and LM and SEM images of pollen grains are also included for the species.